Thomas's Massachusetts, Connecticut, Rhode-Island, New-Hampshire & Vermont Almanack, With an Ephemeris, for the Year of Our Lord 1785: and Ninth of the Independence of America. - Thomas, Isaiah, 1749-1831. (Tufts University. Tisch Library., 2018)
22 leaves [Tisch Library copy contains 18, and contains handwritten annotations]. Essay and narrative content includes: An Account of the First Introduction of Tea into England, and its consequent Expences to the Nation by the Abbe Raynal; Poetical Description of the Boundary Line of the United States.